2023
DOI: 10.1021/acsaem.3c00222
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Overall Water Splitting Reaction Feature on Photodeposited NixP/γ-Ga2O3Nanosheets

Abstract: Solar light-driven overall water splitting for hydrogen production is an ideal solution to climate warming and energy shortage issues. Obtaining a highly efficient and stable photocatalyst remains a major challenge at present. Herein, Ni x P/γ-Ga 2 O 3 nanosheets, which were synthesized from NiCl 2 , NaH 2 PO 2 , and home-made γ-Ga 2 O 3 nanosheets by the photodeposition method under 254 UV irradiation for 30 min, are found as a highly active and durable photocatalyst for pure water splitting into H 2 and O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The FLOSFIA company (Kyoto, Japan) predominantly employs Mist-epitaxy to prepare α-Ga 2 O 3 wafers, and in March 2023, they unveiled an amperage-class 1700 V α-Ga 2 O 3 trench SBD device [45][46][47][48][49]. The cubic spinel structure of γ-Ga 2 O 3 is principally utilized as a photocatalyst for hydrogen production via water splitting [50][51][52][53]. Current research on the cubic perovskite structure of δ-Ga 2 O 3 is comparatively limited.…”
Section: β-Ga 2 O 3 Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FLOSFIA company (Kyoto, Japan) predominantly employs Mist-epitaxy to prepare α-Ga 2 O 3 wafers, and in March 2023, they unveiled an amperage-class 1700 V α-Ga 2 O 3 trench SBD device [45][46][47][48][49]. The cubic spinel structure of γ-Ga 2 O 3 is principally utilized as a photocatalyst for hydrogen production via water splitting [50][51][52][53]. Current research on the cubic perovskite structure of δ-Ga 2 O 3 is comparatively limited.…”
Section: β-Ga 2 O 3 Materialsmentioning
confidence: 99%
“…Materials 2024, 17, x FOR PEER REVIEW 3 of 34 γ-Ga2O3 is principally utilized as a photocatalyst for hydrogen production via water splitting [50][51][52][53]. Current research on the cubic perovskite structure of δ-Ga2O3 is comparatively limited.…”
Section: β-Ga 2 O 3 Materialsmentioning
confidence: 99%
“…Ga 2 O 3 has been investigated as a good photocatalytic material for water splitting [38] and photocatalytic CO 2 reduction. [39] However, because there are fewer CO 2 reduction sites on the surface, its selectivity for CO production is only 60 % even after loading Ag.…”
Section: Photoabsorption Enhancementmentioning
confidence: 99%
“…Li et al reported a ZnIn 2 S 4 /CdS hollow core-shell nano-heterostructure with an appropriate potential gradient and Zn/In bimetallic synergism, showing improved carrier transportation properties [19]. Research has revealed that constructing heterojunctions between two or more semiconductors results in the creation of a potential gradient and an internal electric field, which serves as an effective method for the separation of electrons and holes [20,21]. However, previous studies have mainly considered semiconductor bandgap width matching, whose perspective of structural matching has not been investigated as thoroughly.…”
Section: Introductionmentioning
confidence: 99%